Analysis of Waste in Clinical Pathology Laboratory Services Using a Lean Management Approach at RSAU dr. Esnawan Antariksa in 2025 - Oktariani, Hana; Indrawati, Lili; Aziz, Abdul (International Journal of Business, Law, and Education, 2025)
Lean management is a strategic framework designed to minimize waste and enhance efficiency across all aspects of production or service delivery within an organization. This study aims to analyze how the implementation of lean management can minimize waste in clinical pathology laboratory services at RSAU dr. Esnawan Antariksa. A mixed-method approach was employed, integrating qualitative and quantitative research within a descriptive analytical framework at RSAU dr. Esnawan Antariksa. The findings are presented in two sections: qualitative results, which include waste identification and Root Cause Analysis (RCA), and quantitative results derived from questionnaires indicating that six out of seven types of waste were identified in the clinical pathology laboratory—namely, defect, overproduction, transportation, waiting, inventory, motion, and overprocessing. The RCA revealed repeated sampling as a key underlying issue. Based on efficiency time analysis, waiting times at the registration desk and during laboratory result verification were associated with a low Process Cycle Efficiency (PCE) of 47%. The study recommends adding registration desks and implementing a Laboratory Information System (LIS) to reduce delays in laboratory result processing. In conclusion, six out of seven types of waste were found in the clinical pathology laboratory at RSAU dr. Esnawan Antariksa. Through the calculation of weighted percentages to assess the impact of each waste type, the strongest relationship was found between overprocessing and overproduction wastes (19.80%). Overprocessing waste—particularly in repeated blood sampling—was identified as the primary concern. Therefore, regular training for analysts responsible for sample collection is recommended to reduce waste and improve laboratory efficiency.